Anatomical and functional efficacy of radial scleral buckling and combined laser and surgical intervention for local macula-on retinal detachment - M.R. Taevere; L.A. Kryl; A.V. Doga; D.O. Shkvorchenko (РМЖ "Клиническая офтальмология")
M.R. Taevere, L.A. Kryl', A.V. Doga, D.O. Shkvorchenko S. Fyodorov Eye Microsurgery Federal State Institution, Moscow, Russian Federation Aim: to compare anatomical and functional outcomes of scleral buckling (SB) and combined laser and surgical intervention for focal macula-on rhegmatogenous retinal detachment (RRD). Patients and Methods: surgical outcomes of 84 patients (84 eyes) with focal RRD were analyzed. The study group included 43 patients (43 eyes) who underwent combined laser and surgical treatment for RRD that involved Nd:YAG laser excision of vitreoretinal adhesions followed by pneumoretinopexy and barrier laser photocoagulation. The control group that included 41 patients (41 eyes) was a retrospective sample of patients who underwent radial SB as described. Anatomical (the number of patients with attached retinal after a single surgical intervention and recurrence rate after surgery) and functional efficacy of the surgery were compared over a 2-year follow-up. Results: complete retinal reattachment was reported in 40 patients (93%) in the study group and 39 patients (95.1%) in the control group. Recurrent RD occurred in 3 patients (7.5%) in the study group and 4 patients (9.7%) in the control group over a 2-year follow-up. After 2 years, the final anatomical efficacy was 86% in the study group and 85% in the control group. Notably, no recurrent RD at the site of surgery was reported in the study group. Meanwhile, recurrent RD in the area of the primary retinal tear was reported in 1 patient in the control group. When comparing functional outcomes between the groups, a significant decrease in BCVA accounted for by an increase in astigmatism and spherical equivalent was reported after SB. Conclusions: the combined laser and surgical treatment is not inferior to SB in terms of anatomical efficacy and significantly superior to SB in terms of functional efficacy due to no changes in refractive indices after surgery. Keywords: rhegmatogenous retinal detachment, optical coherence tomography, YAG laser retinotomy, vitreoretinal traction, treatment, recurrence. For citation: Taevere M.R., Kryl L.A.', Doga A.V., Shkvorchenko D.O. Anatomical and functional efficacy of radial scleral buckling and combined laser and surgical intervention for local macula-on retinal detachment. Russian Journal of Clinical Ophthalmology. 2023;23(3):119–123 (in Russ.). DOI: 10.32364/2311-7729-2023-23-3-2.